2009
DOI: 10.1590/s1806-83242009000400015
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of two fluoride varnishes on white spot lesions: a randomized clinical trial

Abstract: The aim of this randomized clinical trial study was to evaluate the therapeutic effect of two varnish formulations (G1 = 5% NaF, G2 = 6% NaF + 6% CaF(2)) on the remineralization of white spot lesions (WSL). The sample was composed of 15 (7- to 12-year-old) children with 45 active WSL in anterior permanent teeth. The children were randomly divided into two groups providing 22 lesions for G1 and 23 for G2. The children were submitted to weekly varnish applications 4 times. The WSL were evaluated twice: baseline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
43
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 19 publications
8
43
0
2
Order By: Relevance
“…This finding corroborates those of previous studies (6,10,12,16,18,19). There was a 45.7% reduction in WSL size, which is in agreement with previous studies (9,10,12,16).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding corroborates those of previous studies (6,10,12,16,18,19). There was a 45.7% reduction in WSL size, which is in agreement with previous studies (9,10,12,16).…”
Section: Discussionsupporting
confidence: 93%
“…Similar results were found in the in vivo and in vitro study carried out by Slade et al (20), comparing Fluorniz, Durafluor and Duofluorid was well as in the in vivo study carried out by Ferreira et al (16), who assessed Duraphat and Duofluorid XII fluoride varnishes.…”
Section: Discussionsupporting
confidence: 88%
“…This is an intervention study developed in the form of a randomized clinical trial according to the fluoride varnish applied that evaluated 60 children of both sexes aged from 06 months to 5 years assisted in the "Só-Riso" Project -Mother and Child Care, Dental School, Federal University excluded from the study [9]. Parents / guardians received guidance on practices favorable to the maintenance of oral health such as diet and oral hygiene, especially on brushing with small amount of fluoridated toothpaste twice a day.…”
Section: Methodsmentioning
confidence: 99%
“…Although the use of FV does not completely prevent the development of caries lesions, their reduced incidence and depth should be considered (1). Previous studies have demonstrated the possibility of stoppage of incipient lesions through their inactivation after the fourth FV application, thereby excluding the need for invasive restorative treatment [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation